Family Communication Patterns in Gender Relations in Coastal and Mountain Communities in Aceh - Marhamah; Irwanto; Fauzi; Shafira Ulfa Rahmani; Sufri Eka Bhakti (Muwazah, 2022)
This research examines gender relations and family communication patterns to maintain harmony in coastal and mountain communities in Aceh. This research is a qualitative research with a phenomenological approach. Data collected by means of interviews, observation, FGD and documentation, informants 10 families in North Aceh District and 10 families in Central Aceh District. The validity of the data was obtained using source triangulation techniques and data analysis using the Miles and Huberman model analysis starting from data reduction, display and data verification. The results of the study show gender relations in mountain communities in the division of roles in implementing gender partnerships. Coastal communities differentiate the roles of women in the domestic sphere and men in the public sphere, and are adaptive to certain conditions. In the aspect of decision making, there are similarities, namely it is in the hands of the man (head of the family), although other family members are included in the deliberations. Family communication patterns in coastal communities are patterns of equality and separate unbalanced patterns. The pattern of communication in mountain communities applies a separate balanced pattern which is internalized in the manganese iyo tradition. This communication pattern creates an attitude of mutual understanding, openness and mutual trust which has an impact on the realization of harmony in the family so as to reduce the divorce rate.